PENGEMBANGAN MODUL AJAR BERORIENTASI BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Zunaidi, Ach.; Masyhud, M. Sulthon; Suroyo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research was motivated by students' difficulties in understanding abstract mathematical concepts and teachers' lack of varied learning strategies, so a Blended Learning-oriented Teaching Module was needed so that it could be accessed by students online and face-to-face to provide a different learning experience. The aim of the research is to describe the validity, practicality and effectiveness of the Blended Learning-oriented Teaching Module in improving the mathematics learning outcomes of third grade elementary school students. The type of research used is R&D with the Borg & Gall model which consists of ten stages, namely (1) Introduction, (2) Product planning, (3) Initial product development, (4) Product validation, (5) Product revision, (6) ) Usage trials, (7) Product revisions, (8) Practicality and effectiveness trials, (9) Final and mass products, and (10) Product dissemination and implementation. Based on the research results, it can be concluded that the validity of the Blended Learning-oriented Teaching Module meets the appropriate criteria with a score of 82.85. After meeting the validity criteria, the Blended Learning-oriented Teaching Module was tested in the field with the results that the practicality of the Blended Learning-oriented Teaching Module was declared very practical with a score of 86.59 and the effectiveness of the Blended Learning-oriented Teaching Module obtained the highest percentage of 88% or 21 students obtained a score range of 81 -100. By referring to these results, the researcher provides suggestions that the use of Blended Learning-based Teaching Modules can be expanded in scale considering their high level of practicality and effectiveness. However, users must also pay attention to the completeness of facilities and infrastructure so that the implementation of Blended Learning-oriented Teaching Modules can run optimally.